2008
DOI: 10.1111/j.1440-172x.2008.00703.x
|View full text |Cite
|
Sign up to set email alerts
|

Ritual: The final expression of care

Abstract: Hospice nurses know that all their patients will die. There are several potential benefits of including rituals and healing practices into the hospice care setting for staff. Evidence suggests that not only does it provide an outlet for hospice workers to express their grief and reflect on their work in an accepting environment; providing closure for their patient's passing but it has also been shown to decrease the risk of burnout and compassion fatigue. This article discusses the important aspects of grief r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Nurses have noted the difficulty of being close with families and regularly being around death at work (Running et al . ). They often feel emotional containment is necessary.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Nurses have noted the difficulty of being close with families and regularly being around death at work (Running et al . ). They often feel emotional containment is necessary.…”
Section: Introductionmentioning
confidence: 97%
“…Emotional distress can span many different kinds of situations as nurses experience their own emotions while witnessing and attending to the emotions of patients and families. Nurses have noted the difficulty of being close with families and regularly being around death at work (Running et al 2008). They often feel emotional containment is necessary.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Work-life balance, education, work interventions (support groups and interventions) spiritual support and self-care and selfefficacious opportunities are some of the ways that people who are experiencing empathy burnout can be restored. Webb (2014) found that the creation of a "Spiritual Formation Group" for hospice workers was similar to groups described in research undertaken by Running, Tolle, and Girard (2018) and (Castle & Phillips, 2003). The purpose of these groups was to give hospice care professionals a platform to express their grief toward the loss of their patients and to provide mutual support (Webb, 2014).…”
Section: Empathy Developmentmentioning
confidence: 94%
“…In such cases, rather than accepting the death and the transformation of the relationship into an internalized one [Bowlby, 1980;Field, 2006], the bereaved experiences a blurring of the boundaries between the living and the dead, with the physical presence of the deceased continuing to be sought years after the loss has occurred [Field, 2006;Gupta and Bonanno, 2011;Klass, 1996]. Other maladaptive forms of continuing bonds involve writing or talking to the deceased long after their death, wearing or carrying a symbolic reminder of the deceased, using possessions for embodying the deceased in order to maintain the illusion of physical contact [Running et al, 2008], or stalking a former romantic partner online [Sas and Whittaker, 2013].…”
Section: Rituals Of Letting Go In Grief Therapymentioning
confidence: 99%